Calcium polysulfide remediation of hexavalent chromium contamination from chromite ore processing residue - Graham, Margaret C.; Farmer, John G.; Anderson, Peter; Paterson, Edward; Hillier, Stephen; Lumsdon, David G.; Bewley, Richard J.F. (The Science of the total environment, 2006)
Past disposal of high-lime chromite ore processing residue (COPR) from a chemical works in S.E. Glasgow, UK, has led to continuing release of toxic and carcinogenic hexavalent chromium (Cr(VI)) to groundwaters which are highly contaminated with Cr(VI)O 4 2−. Traditional methods of remediating Cr(VI)-contaminated land, e.g. using ferrous sulfate and organic matter, have had limited success in converting Cr(VI) to less harmful and insoluble Cr(III). This paper describes the first application of calcium polysulfide (CaS x ) to the remediation of contaminated groundwater and high-lime COPR in a series of laboratory experiments, which have demonstrated the effectiveness of the treatment in quantitatively and rapidly reducing Cr(VI) to Cr(III) over the pH range (8–12.5) typically found at the sites. Cr(III)-organic complexes, present in groundwater at one location, were also effectively precipitated upon treatment with CaS x . The potential for large-scale use of CaS x in the remediation of Cr(VI) from COPR is also discussed.